Gender and candidate communication : videoStyle, webStyle, newsStyle - Bystrom, Dianne G. (Gender politics, global issues., 2004)
A poll as recently as 2000 revealed that one third of the population thinks 'there are general characteristics about women that make them less qualified to serve as president'. As the public and the media rely on long-held stereotypes, female candidates must focus even harder on the way they want to define their own image through traditional mass media, such as television, and new forms, such as the internet. VideoStyle, WebStyle, NewStyle digs deep into the campaigns of the last decade sifting through thousands of ads, websites, and newspaper articles to find out how successful candidates have been in breaking down these gender stereotypes.; Among their findings are that female candidates dress more formally, smile more, act 'tougher' when they can, and prefer scare tactics to aggressive attack ads. This book also presents the most comprehensive, systematic method yet for identifying and understanding self-presentation strategies on the web. The internet may be the medium of the future, but Bystrom has found that coverage on the web tends to draw even more heavily on old stereotypes.